2019
DOI: 10.1080/23322969.2018.1564353
|View full text |Cite
|
Sign up to set email alerts
|

The affective economy of internationalisation: migrant academics in and out of Japanese higher education

Abstract: Internationalisation is a polyvalent policy discourse, saturated in conceptual and ideological ambiguity. It is an assemblage of commodification, exploitation and opportunity and is a container for multiple aspirations, anxieties, and affordances. It combines modernisation, detraditionalisation, and expansiveness, with knowledge capitalism, linguistic imperialism, and market dominance. There are notable policy shadows and silences, especially relating to the emerging subjectivities, motivations and narratives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…(2007: 153) There exists scholarship on transnational migration patterns and the movement of scholars from/of the Global South. There are also discussions about the sociopolitical impacts of such academic migration upon the Global South, as well as impacts upon the migrants themselves as they adjust to unfamiliar academic and societal cultures in the Global North (Cantwell and Lee 2010;Hallett and Eryaman 2014;Maadad 2014;Morley et al 2019). In a study conducted amongst Non-English-Speaking Background (NESB) international academics in Australia, stresses that affected their experiences were identified (Maadad 2014).…”
Section: Race Migration and The Global Visa Regime In Academiamentioning
confidence: 99%
“…(2007: 153) There exists scholarship on transnational migration patterns and the movement of scholars from/of the Global South. There are also discussions about the sociopolitical impacts of such academic migration upon the Global South, as well as impacts upon the migrants themselves as they adjust to unfamiliar academic and societal cultures in the Global North (Cantwell and Lee 2010;Hallett and Eryaman 2014;Maadad 2014;Morley et al 2019). In a study conducted amongst Non-English-Speaking Background (NESB) international academics in Australia, stresses that affected their experiences were identified (Maadad 2014).…”
Section: Race Migration and The Global Visa Regime In Academiamentioning
confidence: 99%
“…This results in the early career Chinese scholars and families in her study having to continually negotiate and make sense of their unstable class position(ings) at each juncture along their mobility trajectories. Morley, Leyton and Hada's (2019) contribution is another exemplar of translocational positionality. They found that the policy discourses, processes, and practices of internationalisation led to diverse affective engagements among their academic expatriate participants who come from different ethnicities.…”
Section: Diversity Intersectionality and Translocational Positionmentioning
confidence: 99%
“…Morley, Leyton and Hada's () contribution is another exemplar of translocational positionality. They found that the policy discourses, processes, and practices of internationalisation led to diverse affective engagements among their academic expatriate participants who come from different ethnicities.…”
Section: Diversity Intersectionality and Translocational Positionalitymentioning
confidence: 99%
“…Tension existed between policy aspirations to internationalise and micropolitical resistance to linguistic imperialism (Morley et al 2019 ). Gottlieb ( 2005 : 75) also describes a ‘tension between two arms of internationalisation policy—teaching English and promoting the spread of Japanese’.…”
Section: Deep and Surface Internationalisation: Joining The Global Comentioning
confidence: 99%
“…An assemblage is a multiplicity of interacting forces and components involving fluidity, exchangeability and multiple functionalities (Deleuze and Guattari 2008;Nail 2017). The assemblage of internationalisation can include an underbelly or shadow relating to market values, male, colonial and ethnic dominance, commodification and disposability of academic labour, linguistic imperialism and knowledge capitalism (Morley et al 2018(Morley et al , 2019. Unsticking oneself, or becoming a fluid subject, can produce affective assemblages relating to belonging, inclusion/exclusion and difference.…”
Section: Academic Mobility: Material Intellectual and Affective Transitionsmentioning
confidence: 99%